Bitten by the System that Cared for them: Towards a Trauma-Informed Understanding of Patients' Healthcare Engagement. Issue 5 (20th October 2021) - Selwyn, Candice N.; Lathan, Emma C.; Richie, Fallon; Gigler, Margaret E.; Langhinrichsen-Rohling, Jennifer
ABSTRACT: The BITTEN theoretical framework of trauma-informed healthcare proposes that each patient presents to a healthcare encounter with a baseline level of historical institutional B etrayal and trauma exposure that interacts with their I ndicator for healthcare engagement to potentially T rigger trauma symptoms, impacting patients' T rust in healthcare providers and shaping their current and future E xpectations of and N eeds for healthcare. The current study sought to test and extend components of the BITTEN theoretical framework to better understand the link between trauma exposure (childhood trauma and institutional betrayal) and healthcare engagement. Results largely supported the propositions of the BITTEN theoretical framework: childhood trauma was directly related to healthcare avoidance behaviors. The relation between childhood trauma and healthcare avoidance was partially mediated by patients' reduced trust in healthcare providers. Further, the relation between childhood trauma and reduced trust in healthcare providers was potentiated by experiences of institutional betrayal. Interpreting patients' interactions with healthcare providers and the healthcare system as a whole in light of their interpersonal and institutional trauma histories is needed to more fully embody trauma-informed healthcare. The BITTEN theoretical framework of trauma-informed healthcare appears to be a viable foundation for developing a trauma-informed understanding of patients' healthcare engagement.